Reliability and Validity of the Lactate Pro 2 Analyser - Mahony, Nicholas; Fleming, Neil; Boland, Marie; Crotty, Nora May Nuala; Donne, Bernard (My University, 2021)
This study evaluated the reliability of the portable Lactate Pro 2 analyzer (LP2), and its validity compared to a laboratory-based analyzer, YSI 1500 Sport (YSI). Blood samples (n = 258) were collected during 44 graded incremental rowing tests, with data from 17 tests used to quantify load, heart rate, and oxygen consumption at lactate threshold. Inter-LP2 reliability was high with coefficient of variation = 3.3%; Bland Altman 95% limits of agreement varied from ± 0.3 mmol.L−1 for blood lactate (BLa) ≤4.0 mmol.L−1 to −1.6 to +1.4 mmol.L−1 for BLa >8.0 mmol.L−1, with minimal systematic bias. Despite LP2 measurements being ~1.42 times higher than YSI measurements, no significant differences (P > .05) were detected when quantifying load, heart rate, or oxygen consumption data at lactate threshold. The results support using different LP2 devices interchangeably, especially when BLa ≤ 8 mmol.L−1, and using the LP2 to identify training intensities at lactate threshold.
Keywords: YSI 1500 Sport; Portable lactate analyzers; Lactate threshold; Bland- Altman limits of agreement; Dmax; Physiology; Sports Science